Aplicación de técnica de fisioterapia respiratoria en el tratamiento de bronquitis aguda en niños 2-5 años, Subcentro de Barrio Lindo Provincia de Los Ríos Cantón Babahoyo periodo mayo - septiembre 2019. - Peralta Barreto, Leidy Elizabeth (2019)
The objective of the present study was to determine that the application of respiratory physiotherapy techniques helps in the treatment of acute bronchitis of children 2 to 5 years old who attend the Barrio Lindo Subcenter. The descriptive, quantitative, field methodology was applied, using the survey applied to the parents of these children, whose results showed that 56% of infants belong to the female gender, two thirds (68%) are older than 2 years, the type of bronchitis that prevailed in two thirds (65%) was acute, whose diagnosis time was more than 6 months in 58%; the majority of parents (54%) complained that their children did not show a rapid improvement, largely because the equipment used was not adequate (61%), did not use protocol procedures (56%), despite this, they observed compliance with certain biosafety standards such as hand hygiene (84%) and use of personal protective equipment (69%). In conclusion, the majority population expressed their general agreement to strengthen the procedure to perform respiratory physiotherapy, based on a protocol guide, to improve the care of children with bronchitis in the health establishment.